REVITALISASI EMPING MELINJO DAN SATE BANDENG BERBASIS LOCAL FOOD DIVERSIFICATION GUNA MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KOTA SERANG PROVINSI BANTEN - Ranthy Pancasasti; Natiqah Natiqah; Ana Susi Mulyani; Elmie Hanafi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Banten Province has a variety of regional specialties, including Sate Bandeng and Emping Melinjo. But now, the typical Banten food is starting to get a little bit of interest. Therefore, the PPM team created a program based on Local Food Diversification for Banten specialties. The method/approach used is participatory, starting from planning, implementation to evaluation, for example through seminars, workshops, field meetings, coaching as well as through printed information media and IT-based electronic media. The results of this PPM are in the form of a documentary on the YouTube Channel and content on social media about Emping Melinjo and Sate Bandeng, in order to participate in assisting government programs, promoting Emping Melinjo and Sate Bandeng to remain sustainable and known to foreign countries.